On Contact and Continuity: The Boundaries Between Things - Nuñez, Gonzalo (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This work carries out a metaphysical study on the notions of contact in terms of boundaries from an ontology of material objects. Two things are in contact when their boundaries (or parts of them) spatially meet. Relationalism and substantivalism are taken as two accounts about contact regarding their quantificational commitments on space. However, since according to discoveries from quantum physics it is possible to discard the idea of contact in physical space, the discussion needs to be set in a topological continuous space. It is then required to solve the incompatibility between the existence of continuous space and the existence of boundaries as a sort of discontinuity. Four theses are evaluated: classic view, overlapping view, gappy view, and coincidence view. Unlike the others, the latter is defended because it does not give up to fundamental ontological features of boundaries and is the least arbitrary about their belongingness.
Keywords: boundary; contact; space; continuity; material objects